Location tracking using LoRa - Norlezah Hashim; Fakrulradzi Idris; Tuan Nur Anisa Tuan Ab Aziz; Siti Halma Johari; Rozilawati Mohd Nor; Norfariza Ab Wahab (Institute of Advanced Engineering and Science, 2021)
Local area network (LAN) as Bluetooth, WiFi and ZigBee are well established technology. The biggest problem with many LAN is the battery consumption and short ranges link budgets. LoRa is a new, private, unlicensed and spread spectrum modulation technique which allows sending low rates at extremely long ranges with minimal power consumption. More importantly, there is no access fee associated with this type of wireless technology. The main idea behind this work is to conduct performance and capability analysis of a currently available LoRa transceiver. We develop a location monitoring system using LoRa and global positioning system (GPS) module and we analyze the detectable range of its data, its battery consumption as well as received signal strength indicator (RSSI). Our deployment experiment demonstrates that the system is able to detect the transmitted data within 290 meters of distances. Using 6 volts of battery AA, the transmission of data still occurred after 24 hours. This project is emphasized a location monitoring system that provide low power usage but long range.